HUBUNGAN KECERDASAN SPIRITUAL DENGAN GEJALA DEPRESI LANJUT USIA DI KELURAHAN DEMANGAN KECAMATAN GONDOKUSUMAN YOGYAKARTA - , DIMAS NURMAAFI, Purwanta, S.Kp., M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Indonesia is facing a double burden. Not only the face of the increasing birth rate, but also cope with the increasing number of elderly people (60 years and over). Increased physical diseases, psychosocial factors and brain aging process, all contribute to the high prevalence of depression in the elderly. In addition to the changes in the elderly can lead to depression. Whereas in the case of the elderly experiencing spiritual growth. Good progress in the spiritual aspect can make the elderly more able to make sense of life and have self-acceptance to the conditions that give a positive response to the changes that occur in the elderly. Objective: To determine the relationship of spiritual intelligence with depressive symptoms in the elderly in the Village District Demangan Gondokusuman Yogyakarta. Methods: The study was observational with cross sectional research design. The research was carried out in March in the Village District Demangan Gondokusuman Yogyakarta. Instruments used are questionnaires. The sampling method used was purposive sampling. Sample was 88 people. Data analysis using the Spearman Rank Test. Results: The results of statistical tests indicate that spiritual intelligence have a significant association with depressive symptoms (p = 0.000 and r = -0.702) Conclusion: Spiritual intelligence has a relationship with depressive symptoms